Heavy Metal Accumulation in Industrial Solid Waste Amended Soil. - Y. SONAWANE, V. (Asian Journal of Chemistry, 2010)
The accumulation of Zn, Pb, Cu, Hg, As, Cr, Cd and Ni in industrial solia waste amended soil profiles was determined. The soil samples were taken at a depth of 10-15 cm from the surface. The status of the metals in seven different samples was determined. All samples were collected from different locations on polyethylene sheets and allowed to dry in air at ambient temperatures. The concentration of these metals was detected by atomic emission spectroscopy. The concentration of some metals was found to be higher.